Analisa Keausan Kampas Kopling Serat Serabut Kelapa Dengan Matrix Epoxy Resin - Marja, R I; Junaidi; Nasution, F A K (Cered Indonesia Institute, 2024)
The aim of this research is to determine the wear rate of clutch linings using coconut fiber and to compare the quality of clutch linings made from asbestos with clutch linings made from coconut fiber and a mixture of fiberglass fibers. The materials used in this research were copper powder, aluminum powder, coconut fiber and epoxy resin. Then, during manufacture, a manual specimen printing process is carried out using a mold that has been designed and a manual pressing process is carried out on specimens weighing +- 80kg. After obtaining six clutch lining specimens varying from copper powder, aluminum powder, coconut fiber and epoxy resin, a wear testing process was carried out, then a comparison of the data from the wear test results and the properties of each material for making the clutch lining specimens was carried out. The results of this test show that the composition of the material with a heavy fraction of copper powder of 25%, aluminum powder of 25%, coconut fiber of 50%, fiber of 25% and Epoxy resin of 50% obtained a dry test wear value of 2.9 mm and a dry test wear value of 2.9 mm. wet test the effect of oil is 3.7 mm. So it is close to the price of clutch linings for motorbikes with a dry test wear price of 2.2 mm and a wet test wear price influenced by oil of 2 mm, where coconut fiber can be used to make clutch linings.